Sistem Kompensasi Polri melalui Beasiswa sebagai Benefit Adaptif terhadap Dinamika Sosial - Rahmadyanto, Sopian (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
The compensation system within the Indonesian National Police (Polri) organization focuses on financial aspects, which are oriented towards the distribution of basic salaries, allowances, and incentives. This orientation towards purely financial compensation is limited in its ability to respond to the complex social dynamics of the era of globalization, which demands credibility, competence, and adaptability from Polri personnel. This study aims to explore the potential of providing non-financial benefits such as scholarships as a means of adaptation and a focus on the long-term orientation of the Indonesian National Police organization. This study uses a literature study approach with secondary data sourced from academic journals, government publications, and other relevant documents, which are analyzed descriptively. The results of this study show that the compensation system in the Polri organization is still dominated by the dimension of financial compensation, in which case there is an urgency to integrate scholarships as a reward for self-development. The implementation of scholarships faces structural and cultural challenges as well as budget constraints, but the scholarship provision strategy has the potential to strengthen the intellectual, professional, and social capacity of Polri individuals in facing the social dynamics of society. The implications of this research focus on the need to reformulate Polri's compensation policy through the formal integration of scholarships as a long-term investment instrument for human resource development.